Study on viscosity induced contrast in ultrasound color flow imaging of carotid atherosclerosis - A. B. M. Aowlad Hossain; Dabasish Kumar Saha; Zubair Ahmed Ratan (Institute of Advanced Engineering and Science, 2021)
Efficient imaging of blood flow disturbances resulted from carotid atherosclerosis plays a vital role clinically to predict brain stroke risk. Carotid atherosclerosis and its development is closely linked with raised blood viscosity. Therefore, study of viscosity changing hemodynamic effect has importance and it might be useful for improved examination of carotid atherosclerosis incorporating the viscosity induced contrast in conventional ultrasound imaging. This work considered the design of realistic models of atherosclerotic carotid artery of different stages and solved to compute the hemodisturbances using computational fluid dynamics (CFD) by finite element method (FEM) to investigate viscosity changes effect. Ultrasound color flow image of velocities of blood have been constructed using phase shift information estimated with autocorrelation of Hilbert transformed simulated backscattered radiofrequency (RF) signals from moving blood particles. The simulated ultrasound images have been compared with CFD simulation images and identified a good match between them. The atherosclerosis stages of the models have been investigated from the estimated velocity data. It has been observed that the blood velocities increase noticeably in carotid atherosclerotic growths and velocity distribution changes with viscosity variations. It is also found importantly that the viscosity induced contrast associated to atherosclerosis is detectable in ultrasound color flow imaging. The findings of this work might be useful for better investigation of carotid atherosclerosis as well as prediction of its progression to reduce the stroke risk.